A case of hypokalemia-induced bidirectional ventricular tachycardia. Issue 11 (November 2020) - Xie, Yanan; Han, Jingzhe; Liu, Jinming; Hao, Jie; Zu, Xiuguang; Hao, Yuming
Background: Bidirectional ventricular tachycardia (BVT) is a rare, but serious, arrhythmia. Hypokalemia is commonly found in clinical practice, but hypokalemia-induced BVT has rarely been reported. Case presentation: A 74-year-old male patient with the symptoms of chest distress and palpitations was admitted owing to frequent discharge of his implantable cardioverter defibrillator (ICD) for 4 days. Before admission, the patient experienced diarrhea after intake of crabs, and felt frequent discharge of his ICD with a total of approximately 17 discharges in 4 days. He had no history of digitalis use. The serum potassium level after admission was 3.1 mmol/L and an electrocardiogram was consistent with BVT. The diagnosis was ventricular tachycardia, electrical storm, and hypokalemia. His ventricular tachycardia was completely relieved after correction of hypokalemia. Conclusions: After correction of hypokalemia in this patient, the episode of BVT was terminated and no recurrence of BVT was observed during long-term follow-up. Our findings suggest the diagnosis of hypokalemia-induced BVT.